CEDIL Work-in-Freedom 2 Bangladesh Migration COVID-19 Dataset - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This structured phone survey has been conducted to quantitatively assess the impact of COVID-19 on female labor migrants from the central-eastern districts of Bangladesh, where ILO has been implementing its Work in Freedom phase two (WiF22) since 2019. The WiF-2 program focuses on women migrants in Bangladesh, India, Nepal, Jordan and Lebanon. The survey will guide our understanding of the COVID-19-related risks and options available for female potential migrants and migrant returnees. The survey collected information about migrant women’s overall recent migration experience and their perception about how the spread of the virus have affected their present and future migration plans.